Both novice and expert? How apprentices develop vocational competence in workplaces where technology is continuously changing: Examples from the Norwegian media graphics programme - Nina Aakernes (Nordic Journal of Vocational Education and Training, 2020)
This article explores how young apprentices develop vocational competence through apprenticeship in workplaces where technology is continuously changing. The article draws on results from a longitudinal study that followed seven apprentices enrolled in the media graphics programme in Norway through their two-year apprenticeships.The results showed how the apprentices developed vocational competence in the community of practice in the workplaces by taking an active part in the daily produc-tion, experimenting with different solutions, reflection, and by advice and discussions with their instructors and co-workers. However, the apprentices also had to deal with work tasks where the solutions were not yet known in the workplace. The article shows how the apprentices combined learning from colleagues with learning from other resources such as software courses and use of the internet. The results showed how the apprentices’ competence development can be a resource for the co-workers and can facilitate the development of the enterprise. Furthermore, these results pro-vide new perspectives on competence development in the community of practice. The study showed that the apprenticeship has an innovative potential and is an essential way for young people to develop vocational competence in a world of work where technology is continuously changing.